2018
DOI: 10.5301/tj.5000626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delayed radical cystectomy for invasive bladder tumors on lymph node positivity, cancer-specific survival and total survival

Abstract: Introduction Radical cystectomy (RC) is the main treatment option for patients with muscle-invasive bladder cancer (MIBC) and non-muscle-invasive bladder cancer (NMIBC), which carry the highest risk of progression. In this study, we investigated the effect of time from transurethral resection of the bladder (TUR-B) to cystectomy on lymph node positivity, cancer-specific survival and overall survival in patients with MIBC. Methods The records were reviewed of 530 consecutive patients who had RC and pelvic lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…We identified a total of 30 studies with 32,591 patients ( Table 2 ). There were varied definitions of delay to RC, with 11 studies identifying the “start point” as “diagnosis of bladder cancer” ( 18 28 ), while another 10 used “time of transurethral resection of bladder tumour” (TURBT) ( 6 , 7 , 29 36 ). Five studies evaluated the delay between neoadjuvant chemotherapy and RC ( 29 , 37 40 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…We identified a total of 30 studies with 32,591 patients ( Table 2 ). There were varied definitions of delay to RC, with 11 studies identifying the “start point” as “diagnosis of bladder cancer” ( 18 28 ), while another 10 used “time of transurethral resection of bladder tumour” (TURBT) ( 6 , 7 , 29 36 ). Five studies evaluated the delay between neoadjuvant chemotherapy and RC ( 29 , 37 40 ).…”
Section: Evidence Synthesismentioning
confidence: 99%
“…They found that patients with noninvasive bladder cancer who underwent surgical treatment had an increased incidence of muscle-invasive bladder cancer, which was associated with worse survival outcomes. Türk et al [ 18 ] retrospectively analyzed the case data from 530 patients who underwent radical cystectomy or pelvic lymphadenectomy by selected surgeons between May 2005 and April 2016. They found that patients with early radical cystectomy had better disease-free survival and overall survival time than patients with pelvic lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant number of patients do not respond to NAC, with reported pT0 rates of 38% to neoadjuvant methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) and accelerated MVAC [6,7], as well as pT0 rates of 42% to dose-dense MVAC (ddMVAC) and 36% to gemcitabine, cisplatin (GC) [8]. The NAC nonresponders suffer from unnecessary adverse effects and a delay in time to cystectomy leading to worse overall survival [9,10]. Subsequently, there remains a critical need to understand the molecular biology behind NAC responsiveness, in order to better tailor individual NAC therapy.…”
Section: Introductionmentioning
confidence: 99%